IMPLEMENTASI EKSTRAKURIKULER DRUMBAND DALAM MENINGKATKAN KARAKTER KEDISIPLINAN SISWA SEKOLAH DASAR NEGERI 136 PEKANBARU - Unsya Nurhidayati Azzahra; Zufriady; Zariul Antosa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of implementing drumband extracurricular activities on improving the disciplinary character of fourth-grade students at SD Negeri 136 Pekanbaru. The research was motivated by the low level of student discipline and the need for practical and engaging character education approaches. This study employed a quantitative method using a quasi-experimental time series design. The research sample consisted of 32 students selected through saturated sampling. Data were collected using pretest and posttest questionnaires measuring three indicators of discipline: punctuality and attendance consistency, adherence to rules, and efficiency in time management. The data were analyzed using the Paired Sample t-test and N-Gain analysis. The results showed a significant improvement in students’ discipline after participating in four drumband practice sessions. The Paired Sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest scores. The average N-Gain score was 0.49, categorized as moderate. These findings indicate that drumband extracurricular activities are moderately effective in improving students’ disciplinary character.